Understanding Volcanic Impacts through Time: 4th VICS Workshop, Cambridge, UK, 13-16 April 2019 - Ludlow, Francis (My University, 2019)
The Volcanic Impacts on Climate and Society (VICS; pastglobalchanges.org/vics) working group initiated Phase 2 this year. The aim of Phase 2 is to extend the scope of VICS to major eruptions throughout the Holocene and beyond by exploring evidence of volcanic forcing, testing model experiments, and placing an increased emphasis on archaeological evidence of societal impacts and responses to complement the focus on written records from Phase 1. This year, the meeting – the largest to date – gathered 70 delegates with expertise in history, archaeology, dendrochronology, ice cores, climate modeling, tephrochronology, and volcanology
PUBLISHED
The Volcanic Impacts on Climate and Society (VICS; pastglobalchanges.org/vics) working group initiated Phase 2 this year. The aim of Phase 2 is to extend the scope of VICS to major eruptions throughout the Holocene and beyond by exploring evidence of volcanic forcing, testing model experiments, and placing an increased emphasis on archaeological evidence of societal impacts and responses to complement the focus on written records from Phase 1. This year, the meeting ? the largest to date ? gathered 70 delegates with expertise in history, archaeology, dendrochronology, ice cores, climate modeling, tephrochronology, and volcanology.
Keywords: Volcanic eruptions; Volcanic impacts; Volcanology; Archaeology; History; Dendrochronology; Smart & Sustainable Planet; Irish History; Volcanic Eruptions; explosive volcanism; Environment and housing